Kajian Literatur Tentang Implementasi Pembelajaran Bermakna di Sekolah Menengah Atas - Artha, I N. Widya; Agustini, Ketut; Suartama, I Kadek (Jayapangus Press, 2025)
The transformation of education in the 21st century demands instructional strategies that go beyond cognitive achievement to foster critical thinking, collaboration, and character development. Meaningful learning is considered an appropriate approach to address these challenges. This study aims to identify meaningful learning strategies implemented in Indonesian senior high schools, analyze supporting and inhibiting factors, and reveal research gaps for future studies. A Systematic Literature Review (SLR) method was employed by reviewing sixteen scientific articles published between 2021 and 2024, collected from national and international databases. The findings indicate that dominant strategies include Meaningful Instructional Design (MID), Project-Based Learning (PjBL), Contextual Teaching and Learning (CTL), Cooperative Learning, and Writing to Learn. These strategies have proven effective in enhancing students’ learning outcomes, active engagement, reflection, and character building. The success of implementation is supported by teachers’ readiness, adequate learning resources, and community involvement. However, constraints such as limited teacher training, lack of interdisciplinary innovation, and the absence of comprehensive evaluation standards remain challenges. The literature review also reveals research gaps, particularly the concentration on science subjects, the prevalence of short-term study designs, and the limited exploration of community-based meaningful learning models. In conclusion, meaningful learning significantly contributes to realizing the goals of the Merdeka Curriculum in Indonesia. Nevertheless, future research should focus on developing more contextual, integrative, and sustainable strategies to meet the dynamic needs of 21st century education.